A Promoter Region Polymorphism in PDCD-1 Gene Is Associated with Risk of Rheumatoid Arthritis in the Han Chinese Population of Southeastern China - CuiPing Liu; JueAn Jiang; Li Gao; XiaoHan Hu; FengMing Wang; Yu Shen; GeHua Yu; ZuoTao Zhao; XueGuang Zhang (International Journal of Genomics)
Objective. Programmed cell death 1 (PD-1) induces negative signals to T cells during interaction with its ligands and is therefore a candidate gene in the development of autoimmune diseases such as rheumatoid arthritis (RA). Herein, we investigate the association of PDCD-1 polymorphisms with the risk of RA among Chinese patients and healthy controls. Methods. Using the PCR-direct sequencing analysis, 4 PDCD-1 SNPs (rs36084323, rs11568821, rs2227982, and rs2227981) were genotyped in 320 RA patients and 309 matched healthy controls. Expression of PD-1 was determined in peripheral blood lymphocytes by flow cytometry and quantitative real-time reverse transcriptase polymerase chain reaction. Results. We observed that the GG genotype of rs36084323 was associated with a increased risk for developing RA (OR 1.70, 95% 1.11–2.61, P=0.049). Patients carrying G/G genotype displayed an increased mRNA level of PD-1 (P=0.04) compared with A/A genotype and healthy controls. Meanwhile, patients homozygous for rs36084323 had induced basal PD-1 expression on activated CD4+ T cells. Conclusion. The PDCD-1 polymorphism rs36084323 was significantly associated with RA risk in Han Chinese population. This SNP, which effectively influenced the expression of PD-1, may be a biomarker of early diagnosis of RA and a suitable indicator of utilizing PD-1 inhibitor for treatment of RA.